Comparison of Mortality between Intravenous Albumin and No Intravenous Albumin in Sepsis Patients with Hypoalbuminemia Conditions and Factors that Influence the Mortality of Sepsis Patients - Mochammad Jalalul Marzuki; Supriono; Bogi Pratomo; Syifa Mustika (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Hypoalbuminemia is a strong predictor of mortality in nonoperative and operative patients. Albumin plays a role in maintaining oncotic pressure in critical conditions such as sepsis. The administration of exogenous Human Serum Albumin (HSA) in sepsis with hypoalbuminemia conditions is still controversial with varying outcomes.This study aimed to know the mortality ratio between intravenous albumin administration and no intravenous albumin administration in sepsis patients with hypoalbuminemia conditions and also to know the factors that influence the mortality of sepsis patients.